Outbreak - Cook, Robin, 1940- (Berkley Pub., 1988)
As a deadly plague strikes America, epidemiologist Marissa Blumenthal uncovers the plot behind its spread. Murder and intrigue reach epidemic proportions when a devastating plague sweeps the country. Dr. Marissa Blumenthal of the Atlanta Centers for Disease Control investigates--and soon uncovers the medical world's deadliest secret.